National television broadcasting service in Botswana: the influence of state ownership and funding on the uses of the channel - William Ofentse Lesitaokana; Gaolefufa Joshua Madiba; Kennedy T. Ramojela; Patrick Mosimanegape Lekgetho (Cogent Social Sciences)
This article provides an overview of the development and use of Botswana Television (BTV). It seeks to identify the political economy factors that influence the channel’s operations. Through documentary analysis and in-depth interviews with selected key informants, our findings suggest that BTV is a state-owned channel fully funded by the Botswana Government and has a small advertising market. This inadequate market also subjects the channel to total government funding. Our analysis of data revealed that ownership, funding, and a lack of operational policy at BTV have led to its control by the ruling elite, and an overload of government use of the channel. Although Botswana has reasonable political and economic contexts compared to many other countries in Africa, the State’s ownership and funding of its national television demonstrate a trend of media control that had previously ensued in the global south. The paper argues for a hybrid of both state-funded and public-service broadcasting systems for BTV, as this would reduce uneven control by the ruling elite and significantly align the operations and general use of BTV for the entire public.